인문소양 함양을 위한 교과연계 대면첨삭－건국대 글로컬캠퍼스 글쓰기랩 운영을 중심으로 - 안미영 (교양교육연구, 11(2), 2017)
이 글에서는 건국대학교 글로컬캠퍼스 글쓰기랩에서 실시한 대면첨삭의 의의를 소개했다. 최근 글쓰기 교과는 교육 내실화를 위해 다양한 비교과 프로그램을 운영하고 있다. 대부분의 대학은 클리닉을 비롯한 첨삭활동을 시행한다. 다양한 형태의 글쓰기를 실시하고 그에 대한 피드백이 이루어진다. 건국대 글로컬캠퍼스는 2016년도 1년 동안 읽기-쓰기-면담 활동이 연계된 대면첨삭 비교과 프로그램을 시행했다. 기초교양, 글쓰기와 철학 교과에서 모든 수강생을 대상으로 교과와 연계하여 고전을 읽혔고, 담당 교수는 독후감을 통해 수강생들과 개별 면담을 실시했다. 대면첨삭은 글쓰기의 퇴고활동을 넘어서서 다음과 같은 교육적 가치가 있었다. 첫째, 상담활동을 통해 자신이 읽은 고전에 대한 올바른 이해를 도울 수 있었다. 둘째, 교수와 학생 간 면대면(面對面) 첨삭지도를 통해 생생하고 즉각적인 피드백이 가능했다. 셋째, 교수와 학생간의 친밀감을 쌓는 계기가 되어, 본 수업에서 더 활발한 참여를 유도할 수 있었다. 넷째, 대학 신입생들에게 대학생활지도 및 진로지도의 기회를 제공했다. 대면첨삭은 교수에게 수업 이외 부담이 큰 활동이지만, 학생들에게는 읽기, 쓰기, 대학생활 및 진로지도를 가능하게 하는 활동이다. 온라인 강좌가 성행하는 오늘날에 이르러 대학교육은 학생들에 대한 밀착지도가 절실히 요구된다. ‘의사소통능력’ 향상을 목표로 하는 기초교양교과를 통해 대면첨삭 활동은 더욱 권장될 필요가 있다. This article introduced the significance of face-to-face correction that was conducted in Konkuk University’s glocal campus writing lab. Recently, the writing subject has various extracurricular programs for the improvement of education. Most universities carry out clinics and correction activities. Various types of writing are performed and feedback is provided. Konkuk University’s local campus implemented a face-to-face correction extracurricular program that linked reading, writing and interviewing activities for one year in 2016. Every student read classics in basic liberal arts, writing and philosophy subjects, and the professor conducted individual interviews with the students through subject matter related the book report. Beyond the revision activity of writing, the face-to-face correction had the following educational values. First, counseling activities may help students to understand correctly the classics they read. Second, vivid and immediate feedback was possible through face-to-face correction between professors and students. Third, it was a chance to build a sense of intimacy between the professor and the students, which enabled them to induce more active participation in the class. Fourth, it provided opportunities for college freshmen to lead university life and career guidance. The face-to-face correction is an activity that makes reading, writing, college life, and career guidance possible for students, although it is a big burden other than regular class to the professors. Today, as online courses become more popular, college education demands a close contact with students. Face-to-face correction activities need to be encouraged through basic liberal arts aimed at improving ‘communication skills’. KCI Citation Count: 4